2021
DOI: 10.1111/psyp.13803
|View full text |Cite
|
Sign up to set email alerts
|

Subthreshold error corrections predict adaptive post‐error compensations

Abstract: Relatively little is known about the relation between subthreshold error corrections and post-error behavioral compensations. The present study utilized lateralized beta power, which has been shown to index response preparation, to examine subthreshold error corrections in a task known to produce response conflict, the Simon task.We found that even when an overt correction is not made, greater activation of the corrective response, indexed by beta suppression ipsilateral to the initial responding hand, predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 64 publications
3
9
0
Order By: Relevance
“…Furthermore, electromyography (EMG) recorded even during a choice reaction-time task has also found some degree of subthreshold corrective process. Using a color Simon task, Beatty et al (2021) found that even when an overt correction was not made in response to an error, participants exhibited subthreshold corrective activity which interestingly, predicted post-error performance (i.e., compensatory behavior such as speeding or slowing) on subsequent trials. Similarly, as already discussed, some studies have found evidence of "partial" errors (e.g., Burle et al, 2008;Allain et al, 2009;Cohen and van Gaal, 2014;Ficarella et al, 2019), with some also finding a relationship between these partial errors and post-error behavior (Allain et al, 2009;Ficarella et al, 2019).…”
Section: Consideration Of Errors That Are Not Two-choice Button Pressesmentioning
confidence: 98%
“…Furthermore, electromyography (EMG) recorded even during a choice reaction-time task has also found some degree of subthreshold corrective process. Using a color Simon task, Beatty et al (2021) found that even when an overt correction was not made in response to an error, participants exhibited subthreshold corrective activity which interestingly, predicted post-error performance (i.e., compensatory behavior such as speeding or slowing) on subsequent trials. Similarly, as already discussed, some studies have found evidence of "partial" errors (e.g., Burle et al, 2008;Allain et al, 2009;Cohen and van Gaal, 2014;Ficarella et al, 2019), with some also finding a relationship between these partial errors and post-error behavior (Allain et al, 2009;Ficarella et al, 2019).…”
Section: Consideration Of Errors That Are Not Two-choice Button Pressesmentioning
confidence: 98%
“…Accordingly, error cancellation should already emerge before or during the deflection of the error-related negativity (ERN), which is at odds with the interpretation of the ERN as reflecting the earliest time point of error processing [10,11]. Early error cancellation, however, complements findings on early preparation of error-correction responses that have been reported for manual actions [17,38,39] and visual search behaviour alike [40]. 3 Conflict between the execution and the cancellation of an erroneous response (here: pressing versus releasing a key) might instead contribute to the ERN.…”
Section: Discussionmentioning
confidence: 99%
“…We subtracted the trial-average activity in the time domain from the EEG activity of every single trial, thus effectively removing any phase-locked component, so we could be certain that the resulting oscillatory activity was nonphase-locked, which was not contaminated by ERPs. This method was also widely used in recent EEG studies [ 73 , 74 ].…”
Section: Methodsmentioning
confidence: 99%